(untitled) (Coordinates of Public Administration, 2026)
The article examines the complex issue of ensuring barrier-free accessibility for all citizens, including persons with disabilities, which represents one of the key challenges for the modern service-oriented state. Particular attention is devoted to the interconnection between the historical evolution of the concept of e-government and the development of digital technologies with the formation and implementation of the National Strategy for Creating a Barrier-Free Space. It is demonstrated that the establishment of a barrier-free environment in the digital sphere cannot be considered in isolation from the broader processes of public administration transformation, since digital tools themselves provide the opportunity for equal access to services, information, and communication resources. In this context, the notion of a «unified digital ecosystem» is elaborated, reflecting an integrated environment of state, municipal, and private electronic services functioning as a single network to meet the needs of citizens. Its key characteristics are identified as multi-level systematization, user orientation, cybersecurity assurance, and the capacity to expand functionality in accordance with “life situations.” It is emphasized that orientation toward life situations makes digital services more flexible and adaptive to the real needs of society, while multi-level systematization ensures coherence between different levels of public administration. An assessment is provided of the regulatory documents of the National Agency of Civil Service of Ukraine, aimed at creating an inclusive environment within state authorities and local self-government bodies. Special attention is given to the training program for civil servants on the topic of barrier-free space formation, which seeks not only to enhance professional competence but also to foster a new administrative culture oriented toward the principles of inclusivity. The significance of organically combining digital accessibility and universal design is highlighted as one of the key directions of contemporary state policy on barrier-freeness. Digital accessibility is considered a technical and organizational prerequisite, whereas universal design serves as a conceptual foundation that enables the needs of the widest possible range of users to be taken into account. Such an approach ensures not only equal rights but also an improved quality of life for citizens, creating conditions for their active participation in social life. In conclusion, the article formulates the necessity of systematically integrating the issue of barrier-freeness with the process of digital technology development in public administration. This integration should become a strategic direction of state policy, aimed at building an inclusive society in which every citizen, regardless of physical abilities or social status, has equal access to public services, information, and opportunities for self-realization.